Active Suspension of Truck Seat - Masaaki Kawana; Taro Shimogo (Shock and Vibration)
The driver’s seat of a heavy duty truck is usually mounted on a spring–damper assembly anchored to the cab floor. To improve riding comfort, this study investigated the effects of mounting a computer-controlled actuator in parallel with the traditional spring–damper assembly. A dynamic model of the seat is represented by a two degree-of-freedom system, including a cushion. In this paper, a control system is designed, using optimal control theory, which minimizes rms vertical acceleration at a point representing the driver’s hip point. In this system, accelerations of the hip point, the seat frame and the cab floor are picked up and integrated to obtain the state variables to be fed back and fed forward to the actuator through a digital computer. The actuator is constructed with electric servo-motor and ball-screw mechanism. The experimental study was carried out on a shaker, which simulates the vibrations of the cab floor in actual service. Results were obtained for both a dummy and a real human body. The vibration test produced rms accelerations of the seat and the hip point of about 1.0 m/s2 without the actuator, while the rms accelerations were suppressed to about 0.5 m/s2 at a rms input voltage to the servo-motor of 1.0 V.